(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2022)
We described natural history traits of the brown-banded water snake Helicops angulatus from Eastern Brazilian Amazon, one of the most threatened areas in Amazonia. We recorded morphometric information, feeding habits, and reproductive strategies from 97 mature females, 58 mature males, and 40 juveniles. Females are larger than males, although males have longer tail length. Females and males mature at different sizes, with males becoming mature at smaller sizes. We observed the presence of follicles and secondary eggs throughout the year. However, we found two reproductive peaks, in July and October, corresponding to the dry season in the Amazon region. Diet consists mainly of fishes, followed by frogs that use water bodies for reproduction. Most prey were ingested headfirst (82.35%), possibly to decrease risk of injuries during the capture and ingestion. We found a positive relationship between total length of the prey and snout-vent length of snakes. Compared to other species, H. angulatus ingests proportionally larger prey (22-44% of the snout-vent length of snakes), probably optimizing energy gain.